2019
DOI: 10.1002/eat.23160
|View full text |Cite
|
Sign up to set email alerts
|

Anorexia nervosa and diffusion weighted imaging: An open methodological question raised by a systematic review and a fractional anisotropy anatomical likelihood estimation meta‐analysis

Abstract: Background Anorexia nervosa (AN) is characterized by white matter abnormalities in neuroimaging studies. Fractional anisotropy (FA) is a diffusion tensor imaging (DTI) index that is considered an instrument for the evaluation of white matter alterations. However, the literature has recently pointed out the role of the partial volume effect (PVE) as a confounding factor for the identification of juxtaposed tissues. Our goal was to review the DTI literature in AN and evaluate possible confounding factors linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 79 publications
(165 reference statements)
1
12
0
Order By: Relevance
“…However, the cross-sectional nature of our observations does not allow us to understand whether the observed alterations precede the onset of AN or represent a consequence of the disorder. Moreover, in the computation, we did not control for the potential bias of the partial volume effect and free water due to ventricular enlargement (Kaufmann et al, 2017;Meneguzzo et al, 2019), which, however, are not likely to have a significant effect on the global architecture of the network and on the observed regional alterations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cross-sectional nature of our observations does not allow us to understand whether the observed alterations precede the onset of AN or represent a consequence of the disorder. Moreover, in the computation, we did not control for the potential bias of the partial volume effect and free water due to ventricular enlargement (Kaufmann et al, 2017;Meneguzzo et al, 2019), which, however, are not likely to have a significant effect on the global architecture of the network and on the observed regional alterations.…”
Section: Discussionmentioning
confidence: 99%
“…In the first one, the quantitative voxel-based meta-analysis identified decreased FA in the posterior areas of the corpus callosum, the left superior longitudinal fasciculus (SLF) II and the left precentral gyrus as well as increased FA in the right corticospinal projections and lingual gyrus [31]. In the second one, Meneguzzo et al identified two clusters of decreased FA, in the left corona radiata and in the left thalamus [32]. Finally, more recently, Zhang et al analyzed DTI studies using tractbased spatial statistics (TBSS) and reported lower FA in the corpus callosum and the cingulum [33].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of DTI studies reported that the fractional anisotropy (FA), an indicator of WM integrity, was decreased in the fornix, cingulum, fronto-occipital tract (Monzon et al, 2016), thalamo-cortical tract, and occipital-parietal-temporal-frontal tract (Gaudio et al, 2019). In addition, a systematic review showed decreased FA in the left corona radiata and thalamus (Meneguzzo et al, 2019). Although the number of studies is increasing, results have been inconsistent within imaging modalities, and no convincing interpretations regarding the relationship between regional brain changes and AN pathophysiology have been presented.…”
Section: Introductionmentioning
confidence: 99%